ROLE OF THE AICCRA ACCELERATOR PLAYBOOK IN SHAPING THE WORLD BANK SOIL HEALTH INNOVATION PROGRAM AGENDA - Hauke, Dahl; Peterson, Nathanial Richard (2025)
This report outlines how the AICCRA Accelerator Playbook has informed and shaped the World Bank’s emerging Soil Health Innovation Agenda. It describes how AICCRA’s venture acceleration framework, including science-to-scale pathways, blended finance readiness, and ecosystem alignment, was adapted to the soil health domain. The report highlights lessons that guided the design of the World Bank’s Soil Health Innovation Challenge, the Kenya AgTech Facility, and the technical sprints supporting nine early-stage innovators. It demonstrates how AICCRA’s experience in evidence-based acceleration directly contributed to the World Bank’s soil health innovation architecture, linking research, investment, and policy for climate-smart agriculture.